2019
DOI: 10.1186/s12873-019-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Traffic police officers’ experience of post-crash care to road traffic injury victims: a qualitative study in Tanzania”

Abstract: Background Recently, road traffic injuries (RTIs) have become a major health problem affecting health systems in many low- and middle-income countries. Regardless of whether an ambulance is available for evacuation, police officers have been shown to arrive at the crash scene first, becoming, in effect, the first responders to RTI victims. Therefore, the study aimed to explore the experiences of traffic police officers in regard to the provision of care to RTI victims in the prehospital environ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Police officers have been shown to arrive at the crash scene first, becoming, in effect, the first responders to RTI victims and almost always with a vehicle or the ability to obtain a vehicle expeditiously. Despite a higher frequency of police transportation ([ 55%) following RTI, Boniface et al from Tanzania show increased mortality following police transportation, similar to our study [17]. In Malawi, the police are not trained on essential trauma care, especially for the management of severely injured patients during transport.…”
Section: Discussionsupporting
confidence: 76%
“…Police officers have been shown to arrive at the crash scene first, becoming, in effect, the first responders to RTI victims and almost always with a vehicle or the ability to obtain a vehicle expeditiously. Despite a higher frequency of police transportation ([ 55%) following RTI, Boniface et al from Tanzania show increased mortality following police transportation, similar to our study [17]. In Malawi, the police are not trained on essential trauma care, especially for the management of severely injured patients during transport.…”
Section: Discussionsupporting
confidence: 76%
“…The unaccompanied and unconscious patients at the scene of accident are deemed to have serious injuries. This compares with studies that showed Police officers are usually the first responders at the scene of accident [26,27]. Similarly a study done on post-crash emergency care in India showed good Samaritans and police officers referred about 90% post-crash victims to government hospitals as the first contact health facility [28].…”
Section: Unaccompaniedmentioning
confidence: 89%
“…[ 8 ] Traffic police officers can be important first responders for post crash care; as they step onto the scene, they experience the role of rescuer as well as that of a traffic police officer. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…So if adequately trained in trauma care, the police personnel can significantly contribute to prehospital care. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%